Role of reward structure in creativity and idea fixation - GOH, Jia Hao (Institutional Knowledge at Singapore Management University, 2017)
This study seeks to investigate the role of team reward structures, namely the equity and equality of rewards on team idea fixation, as well as its eventual effects on team idea creativity. Through a manipulation of reward structures, distributions of rewards differ across various teams, and this is expected to result in changes in individual motivation to share ideas within teams. Furthermore, due to the role of motivation in team processes, it is expected that team learning and performance goal orientation would moderate the relationship between team rewards structure and team idea fixation. Results shows that teams in the equality condition are more likely to fixate on ideas than teams in the equity condition. A higher degree of fixation in turn leads to a decrease in creativity of the ideas. No significant moderation of the relationship between team rewards and idea fixation is found for team learning and performance goal orientation.